THE APPLICATION OF YEAST AND LACTIC ACID BACTERIA IMPROVE GROWTH AND INTESTINAL STRUCTURE OF TIGER SHRIMP LARVAE Penaeus monodon Fab. - Muhammadar Abdullah Abbas; Nadhira Alamanda; Ibnu Sahidir; Adrian Damora; Cut Nanda Devira; Dedi Fazriansyah Putra (Universitas Syiah Kuala, 2023)
This study aims to investigate the effect of the different concentration of RABAL (yeast and lactic acid bacteria) probiotics on the survival, feed conversion, growth and intestinal cells changes of tiger shrimp Penaeus monodon Fab. larvae. This study used a Completely Randomized Design (CRD) method with 4 treatments and 4 replications. Tiger shrimp with average size of 0.02 g was randomly stocked in each container containing RABAL with concentration of 0 ppm (A/control), 75 ppm (B), 150 ppm (C), and 225 ppm (D) with frequency once a day for 30 days. Data were analysed using one way ANOVA. The result showed that the application of RABAL with different doses into the shrimp culture media significantly influences (P0.05) the growth and food conversion ratio of tiger shrimp feed but did not significantly affect (P 0.05) on the survival rate. The value of water quality parameters in this study were still at normal levels for tiger shrimp rearing. As conclusion, the application of probiotics RABAL with different concentrations have positive effect on the absolute weight, absolute length, specific growth rate, feed conversion ratio and intestinal villi surface area of tiger shrimp larvae, without adverse effect on the survival rate of tiger shrimp seed.